2018
DOI: 10.1037/spq0000208
|View full text |Cite
|
Sign up to set email alerts
|

State special education criteria for identifying intellectual disability: A review following revised diagnostic criteria and Rosa's Law.

Abstract: Across the last century, the condition known as (ID) has been labeled by assorted terms, its key features have varied, and recommendations for its identification have been divided. In light of recent changes to the diagnostic criteria for ID and to federal legislation, this study was designed to compile and summarize information about the state special education criteria for this condition and its associated assessment process, as they guide school-based and associated practices. Authors independently double-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 7 publications
0
15
0
Order By: Relevance
“…Furthermore, another national survey of 323 school psychologists conducted by Sotelo-Dynega and Dixon (2014) found that 99% of participants administered cognitive tests; of those participants, between 30% and 39% of their time was spent administering and scoring cognitive tests. In light of these findings, the continued inclusion of cognitive tests in decisions about SLD (Maki et al, 2015), and traditional uses of cognitive tests in the identification of intellectual disability and giftedness (McClain & Pfeiffer, 2012;McNicholas et al, 2018), and their use with various other referral concerns (Sotelo-Dynega & Dixon, 2014), it is unsurprising that cognitive test use remains constant in school psychology.…”
Section: The Role Of Cognitive Testingmentioning
confidence: 99%
“…Furthermore, another national survey of 323 school psychologists conducted by Sotelo-Dynega and Dixon (2014) found that 99% of participants administered cognitive tests; of those participants, between 30% and 39% of their time was spent administering and scoring cognitive tests. In light of these findings, the continued inclusion of cognitive tests in decisions about SLD (Maki et al, 2015), and traditional uses of cognitive tests in the identification of intellectual disability and giftedness (McClain & Pfeiffer, 2012;McNicholas et al, 2018), and their use with various other referral concerns (Sotelo-Dynega & Dixon, 2014), it is unsurprising that cognitive test use remains constant in school psychology.…”
Section: The Role Of Cognitive Testingmentioning
confidence: 99%
“…First, tests of cognitive abilities continue to be frequently used in training programs. This emphasis is consistent with professional demands, as reviews of state criteria indicate that assessment of intellectual functioning is widely required when identifying intellectual disability (McNicholas et al, 2018) and giftedness (McClain & Pfeiffer, 2012). Although there is little evidence to support interpretation of cognitive strengths and weaknesses as a supplement to or replacement for a general factor of intelligence (e.g., Beaujean & Benson, 2019), many programs continue to emphasize the assessment of multiple, specific cognitive abilities.…”
Section: Implications For Trainingmentioning
confidence: 77%
“…First, tests of cognitive abilities continue to be frequently used in training programs. This emphasis is consistent with professional demands, as reviews of state criteria indicate that assessment of intellectual functioning is widely required when identifying intellectual disability (McNicholas et al, 2018) and giftedness (McClain & Pfeiffer, 2012). Although there is little evidence to support interpretation of cognitive strengths and weaknesses as a supplement to or replacement for a general factor of intelligence (e.g., Beaujean & Benson, 2019), many programs continue to emphasize the assessment of multiple, specific cognitive abilities.…”
Section: Implications For Trainingmentioning
confidence: 86%